Germination Potential of Safflower (Carthamus tinctorius L.) Against Nickel Heavy Metal - Veli ÇELİKTAŞ; Hande OTU BORLU (ISPEC Journal of Agricultural Sciences)
As a heavy metal, Nickel is also an essential element and an abiotic plant stress factor. Safflower (Carthamus tinctorius L.) is an oil seed plant used commercially for the different industries that belong to the Asteraceae family. This study aims to investigate the effects of nickel concentrations ( 0, 25, 50, 100, 200, 400, 800, 1000 mg kg-1) on safflower germination stages. Germination percentage, germination index and coefficient of velocity equations were calculated according to germinated seeds on days. Nickel concentrations and days after germination were effective on germination percentage, germination index and coefficient of velocity values. Especially 800 and 1000 mg kg-1 nickel doses had a slightly negative effect on the investigated equations. According to the study results, it was thought that the germination ability of C. tinctorius seeds was quite successful in mediums with nickel-heavy metal.